Research trends of traditional Chinese non-pharmacological therapy in the management of overweight and obesity from 2004 to 2023: A bibliometric study - Zhiyuan Bian; Leilei Ren; Jin Bian (Elsevier, 2024)
Objective: Traditional Chinese non-pharmacological therapy has gained popularity in the management of overweight and obesity. This study aims to reveal trends and hotspots of global research on traditional Chinese non-pharmacological therapies for overweight and obesity. Methods: Publications on traditional Chinese non-pharmacological therapies for overweight and obesity between 2004 and 2023 were searched from the Web of Science Core Collection. Bibliometric analyses and visualization were performed using VOSviewer, CiteSpace, and R software. Results: A total of 566 publications from 246 journals were included in this study. Annual number of publications and cited times in the field were generally increasing. China contributed the most publications, followed by the United States and Republic of Korea, and Chengdu University of Traditional Chinese Medicine from China had the highest number of publications among institutions. Stener-Victorin E was not only the most productive author but also, along with Cabioglu MT, the most cited authors. Evidence-Based Complementary and Alternative Medicine was both the largest source journal and the most cited journal. The highly cited references mainly consists of clinical trials, narrative reviews and systematic reviews focusing on acupuncture therapy. Keywords analysis indicated that acupuncture therapy and traditional Chinese exercise constituted the main components of traditional Chinese non-pharmacological therapy in weight management. Conclusions: This study revealed a growing interest in traditional Chinese non-pharmacological therapies for managing overweight and obesity, with acupuncture therapies and traditional Chinese exercises as the main research focuses. This study offers insights into traditional Chinese non-pharmacological therapies in weight management, and may benefit further research.